Systematic Review: Empowerment of Pregnant Women Through "My Plate" (“Isi Piringku”) Education in Stunting Prevention and Nutritional Status Improvement Across the Life Cycle - Basit, Abdul; Said , Laila Refiana (Journal of Scientific Insights, 2025)
Stunting remains a critical public health issue with long-term effects on children's physical and cognitive development. Although the 2024 Indonesian Nutrition Status Survey (SSGI) reported a national stunting prevalence decline to 19.8%, disparities persist, notably in South Kalimantan at 22.9%, surpassing the WHO threshold. Nutritional education for pregnant women through the "My Plate" ("Isi Piringku") initiative is considered a strategic intervention, yet its effectiveness has not been comprehensively reviewed. This study aims to evaluate the effectiveness of "My Plate"-based nutritional education in preventing stunting and improving nutritional outcomes across the life cycle. A Systematic Literature Review was conducted using the PRISMA method, sourcing articles from PubMed, ScienceDirect, DOAJ, and Google Scholar. Inclusion criteria included peer-reviewed articles published between 2015 and 2025 with relevant topics. Data were analyzed using a narrative-thematic synthesis. Most studies employed quantitative experimental or quasi-experimental designs. Nutritional education emerged as the predominant intervention (62.5%), surpassing supplementation and other nutrition-sensitive strategies. "My Plate" education demonstrated positive effects on pregnant women’s nutritional knowledge, attitudes, and practices, and contributed to lowering stunting risk. Key challenges identified included low nutritional literacy, limited food access, and economic constraints. Involvement of husbands and families enhanced behavioral change in dietary practices. In conclusion, "My Plate"-based nutritional education effectively empowers pregnant women to prevent stunting, aligning with Sustainable Development Goals (SDG) 2 (Zero Hunger) and 3 (Good Health and Well-being) by improving maternal and child nutrition and supporting sustainable health outcomes.